2016
DOI: 10.1186/s12913-016-1418-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and preventable acute care spending among a high cost inpatient population

Abstract: BackgroundA small proportion of patients account for the majority of health care spending. The objectives of this study were to explore the clinical characteristics, patterns of health care use, and the proportion of acute care spending deemed potentially preventable among high cost inpatients within a Canadian acute-care hospital.MethodsWe identified all individuals within the Ottawa Hospital with one or more inpatient hospitalization between April 1, 2010 and March 31, 2011. Clinical characteristics and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Several studies have examined the characteristics of HCU, showing that HCU are characterized by the presence of multiple chronic diseases. [8][9][10][11][12][13] Despite this strong association, studies examining specific chronic diseases associated with HCU are very sparse. 1,11,17 One study from 2015, based on The Medical Expenditures Panel Survey which provides a representative estimate of health care use and costs for the US civilian non-institutionalized population, did find the most costly diseases to be cancer, mental disorders, heart diseases, and arthritis, and other non-traumatic disorders 17 which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined the characteristics of HCU, showing that HCU are characterized by the presence of multiple chronic diseases. [8][9][10][11][12][13] Despite this strong association, studies examining specific chronic diseases associated with HCU are very sparse. 1,11,17 One study from 2015, based on The Medical Expenditures Panel Survey which provides a representative estimate of health care use and costs for the US civilian non-institutionalized population, did find the most costly diseases to be cancer, mental disorders, heart diseases, and arthritis, and other non-traumatic disorders 17 which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of HCU has received substantial attention. [7][8][9][10] Previous studies have found HCU to be older, 8,9,[11][12][13] less educated, have low income, 9 and poorer self-perceived health. 8 Another frequently described characteristic of HCU is multimorbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In a recent study of high-cost inpatients within a Canadian acute-care hospital, over half of the patients defined as 'high cost' accumulated costs from a single event, with median total days spent in hospital being markedly higher for high-cost patients compared with nonhigh-cost patients. 5 Given that acute care and ICU spending represent a relatively large proportion of total hospital costs, one might anticipate that reducing LOS would reduce hospital cost. Nevertheless, Taheri et al reported that reducing LOS by one day for all patients admited for at least four days reduced total cost of care by only 2.4% in 1999.…”
Section: Résumémentioning
confidence: 99%
“…Graven et al 17 replicated that analysis, using Oregon's All Payer All Claims database and Medicaid data from the Oregon Health Authority, and found that preventable acute care spending for HC patients accounted for ,6% of their total spending. Using data from Canada, Ronksley et al 18 examined preventable acute care spending among hospitalized HC patients (at the Ottawa Hospital) using an ambulatory care-sensitive conditions algorithm. They found that among the HC inpatient population, most costs were due to a single nonpreventable acute care episode.…”
Section: Introductionmentioning
confidence: 99%